Strategic planning and new product development - Tillman, Frank A., 1937- (FT Press, 2013)
In Strategic Planning and New Product Development , world-class decision support experts Frank A. Tillman and Deandra T. Cassone present a complete corporate strategic planning model for selecting new products: a model that can be used to systematically manage and evaluate business and/or new product opportunities from conception to commercialization. Tillman and Cassone's model captures input on goals and objectives from all levels of the organization, translates these goals and objectives into clear decision criteria, and generates metrics that can be used to measure the success of any decision. It tracks developmental progress of current and/or new business and product opportunities; helps companies eliminate unprofitable business sooner; brings discipline and consistency to evaluating each new opportunity, and generates a list of clear priorities. Tillman and Cassone go beyond "conceptualizing" this model, presenting actual sample computer screens and identifying every key data input, from financial impact and strategic alignment to probability of success. They also demonstrate how to use weighting to bring greater flexibility and agility to decision modeling. Along with offering exceptionally valuable guidance to product developers and corporate strategists, it also demonstrates the broader applicability of automated decision support systems and offers real-world insight for building models that address a wide spectrum of business challenges.